Best Practice Program Corporate Social Responsibility (CSR) PT. Pertamina RU II Production Sungai Pakning - Dadang Mashur (Indonesian Association for Public Administration (IAPA), 2019)
The Commitment of one of the state companies PT. Pertamina in implementing Social and Environmental Responsibility (TJSL) is realized in various CSR activities covering the fields of education, health, environment, infrastructure, community empowerment, disaster management, and special assistance. The realization of activities is carried out by all working units of Pertamina's CSR functions, both at the head office, unit operations, and subsidiaries such as the Sungai Pakning Refinery Unit (RU) II Production. Pertamina implements CSR programs for people, planet and profit (3P) purposes. This goal is the focus of Pertamina in running its operations, where products are developed and services provided care about environmental sustainability, especially the earth for the interests and future of future generations. Pertamina's CSR focuses on four issues that become its pillars, namely: Pertamina Cerdas, Pertamina Sehati, Pertamina Hijau, and Pertamina Berdikari. This article is the result of research conducted with qualitative methods with a participatory approach.